The Gastrointestinal disorders and leaky gut syndrome in endurance athletes - Izabela Murawiec; Magdalena Konert (Journal of Education, Health and Sport, 2023)
Gastrointestinal disorders are common in endurance-sport athletes, and can negatively affect physical performance and general health. During long lasting exercises such like ultramarathon, triathlon, marathon a characteristic phenomenon is the increase in the concentration many proinflammatory markers and proteins such like IL-1, IL-6, TNF-alfa, LPS, CK and C-reactive protein. Despite observed biochemical changes on of the typical “side effects” of physical activity is increased intestinal permeability, also called to as leaky gut.